2014
DOI: 10.1103/physrevd.90.114011
|View full text |Cite
|
Sign up to set email alerts
|

StrongΛbNBandΛcNDvertices

Abstract: We investigate the strong vertices among the Λ b , nucleon, and B meson as well as the Λ c , nucleon, and D meson in QCD. In particular, we calculate the strong coupling constants g Λ b NB and g Λ c ND for different Dirac structures entering the calculations. In the case of the Λ c ND vertex, we compare the result with the only existing prediction obtained at Q 2 ¼ 0.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
73
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 48 publications
0
73
0
Order By: Relevance
“…[18][19][20][21][22][23]. Both radial and p-wave excitations have been also studied in the framework of the QCD sum rules [24][25][26][27][28], in a phenomenological approach [29] and on the lattice [30]. A nonperturbative holographic QCD has been applied to investigate heavy, regular, and exotic baryons in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23]. Both radial and p-wave excitations have been also studied in the framework of the QCD sum rules [24][25][26][27][28], in a phenomenological approach [29] and on the lattice [30]. A nonperturbative holographic QCD has been applied to investigate heavy, regular, and exotic baryons in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The mass and production of the hidden-bottom pentaquarks have been studied in Refs. [4,9,40,[91][92][93][94].…”
Section: Introductionmentioning
confidence: 99%
“…The QCDSR is one of the most powerful non-perturbative methods, which is also independent of model parameters. In recent years, numerous research articles have been reported about the precise determination of the strong form factors and coupling constants via QCDSR, light-cone QCDSR or lattice calculation [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] 2 and qq GG at OPE side. In Sect.…”
Section: Introductionmentioning
confidence: 99%